Small cause, large effect: Structural characterization of cutinases from Thermobifida cellulosilytica. Issue 11 (15th August 2017) - Ribitsch, Doris; Hromic, Altijana; Zitzenbacher, Sabine; Zartl, Barbara; Gamerith, Caroline; Pellis, Alessandro; Jungbauer, Alois; Łyskowski, Andrzej; Steinkellner, Georg; Gruber, Karl; Tscheliessnig, Rupert; Herrero Acero, Enrique; et al.
ABSTRACT: We have investigated the structures of two native cutinases from Thermobifida cellulosilytica, namely Thc_Cut1 and Thc_Cut2 as well as of two variants, Thc_Cut2_DM (Thc_Cut2_ Arg29Asn_Ala30Val) and Thc_Cut2_TM (Thc_Cut2_Arg19Ser_Arg29Asn_Ala30Val). The four enzymes showed different activities towards the aliphatic polyester poly(lactic acid) (PLLA). The crystal structures of the four enzymes were successfully solved and in combination with Small Angle X‐Ray Scattering (SAXS) the structural features responsible for the selectivity difference were elucidated. Analysis of the crystal structures did not indicate significant conformational differences among the different cutinases. However, the distinctive SAXS scattering data collected from the enzymes in solution indicated a remarkable surface charge difference. The difference in the electrostatic and hydrophobic surface properties could explain potential alternative binding modes of the four cutinases on PLLA explaining their distinct activities. Biotechnol. Bioeng. 2017;114: 2481–2488. © 2017 Wiley Periodicals, Inc. Abstract : Differences in electrostatic and hydrophobic surface properties of cutinases from Thermobifida cellulosilytica explain distinct activities on poly(lactic acid).